Knowledge, Attitude, and Practice Towards Responsible Self-Medication Among Pharmacy Students: A Web-Based Cross-Sectional Survey in Uganda - Brian B; Goruntla N; Bommireddy BR; Mopuri BM; Easwaran V; Mantargi MJS; Thammisetty DP; Bukke SPN; Yadesa TM; Ayogu EE (Drug, Healthcare and Patient Safety)
Bukoli Brian,1 Narayana Goruntla,1 Bhavana Reddy Bommireddy,2 Bhavani M Mopuri,2 Vigneshwaran Easwaran,3 Mohammad Jaffar Sadiq Mantargi,4 Durga Prasad Thammisetty,5 Sarad Pawar Naik Bukke,6 Tadele Mekuriya Yadesa,1 Ebere Emilia Ayogu7 1Department of Clinical Pharmacy and Pharmacy Practice, School of Pharmacy, Kampala International University, Western Campus, Ishaka, Uganda; 2Research Scholar, Department of Pharmacy Practice, Raghavendra Institute of Pharmaceutical Education and Research (RIPER) – Autonomous, Anantapur, AP, India; 3Department of Clinical Pharmacy, College of Pharmacy, King Khalid University, Abha, Kingdom of Saudi Arabia; 4Department of Pharmacology, Pharmacy Program, Batterjee Medical College, Jeddah, Saudi Arabia; 5Department of Pharmacy Practice, Sri Padmavathi School of Pharmacy, Tiruchanoor, Tirupathi, AP, India; 6Department of Pharmaceutics and Pharmaceutical Technology, School of Pharmacy, Kampala International University, Western Campus, Ishaka, Uganda; 7Department of Clinical Pharmacy and Pharmacy Management, Faculty of Pharmaceutical Sciences, University of Nigeria, Nsukka, NigeriaCorrespondence: Narayana Goruntla; Bukoli Brian, Department of Clinical Pharmacy and Pharmacy Practice, School of Pharmacy, Kampala International University, Western Campus, Ishaka, Uganda, Tel +256760060453, Email narayanagoruntla@gmail.com; drgoruntla@kiu.ac.ug; bukoli.brian@gmail.comPurpose: Rational self-medication (SM) practice among healthcare students is essential to promote the safe, effective, and economical use of medicines for self-diagnosed conditions. The study aimed to assess pharmacy students’ knowledge, attitude, and practice about responsible self-medication.Methodology: A cross-sectional online survey was conducted among Ugandan pharmacy students for one month from March 1 to March 31, 2024. The study included students enrolled in diploma, bachelor, and master of pharmacy programs in Uganda. Informed consent was obtained online by asking a question regarding willingness to participate. A non-probable snowball sampling technique was used to recruit students. A pre-validated questionnaire was used to obtain socio-demographics, self-medication practices, knowledge, attitudes, and practices about responsible self-medication. We used binary and multivariable logistic regression analysis to identify the factors associated with KAP regarding responsible self-medication.Results: The prevalence of self-medication practice among pharmacy students was 96.73%. The self-medication is most common in headache (78.97%), cold, and cough (79.91%) illnesses. Painkillers (90.19%) and antibiotics (53.97%) are the most common medicines used for self-medication. Most pharmacy students have good knowledge (87.38%) and a positive attitude (96.03%) toward responsible self-medication. However, only 27.34% of students practice rational self-medication. Participants’ university and parents’ professions were significantly associated with good knowledge of responsible self-medication. Whereas factors such as gender, residence, and type of illness were significantly associated with rational self-medication practice.Conclusion: The prevalence of self-medication was high among pharmacy students in Uganda. Painkillers and antibiotics are the most preferred drugs for self-medication. About 87.38% of pharmacy students have good knowledge, and 96.03% have a positive attitude toward responsible self-medication. Rational self-medication practice was low among students. We recommended training sessions to enhance safe self-medication practices among pharmacy students.Keywords: attitude, knowledge, pharmacy students, practices, self-medication, Uganda